Leg length discrepancy in patients with Perthes' disease: a note of caution for the arthroplasty surgeon. (1st November 2021) - Tolk, Jaap J.; Eastwood, Deborah M.; Hashemi-Nejad, Aresh
Abstract : Aims: Perthes' disease (PD) often results in femoral head deformity and leg length discrepancy (LLD). Our objective was to analyze femoral morphology in PD patients at skeletal maturity to assess where the LLD originates, and evaluate the effect of contralateral epiphysiodesis for length equalization on proximal and subtrochanteric femoral lengths. Methods: All patients treated for PD in our institution between January 2013 and June 2020 were reviewed retrospectively. Patients with unilateral PD, LLD of ≥ 5 mm, and long-leg standing radiographs at skeletal maturity were included. Total leg length, femoral and tibial length, articulotrochanteric distance (ATD), and subtrochanteric femoral length were compared between PD side and the unaffected side. Furthermore, we compared leg length measurements between patients who did and who did not have a contralateral epiphysiodesis. Results: Overall, 79 patients were included, of whom 21 underwent contralateral epiphysiodesis for leg length correction. In the complete cohort, the mean LLD was 1.8 cm (95% confidence interval (CI) 1.5 to 2.0), mean ATD difference was 1.8 cm (95% CI -2.1 to -1.9), and mean subtrochanteric difference was -0.2 cm (95% CI -0.4 to 0.1). In the epiphysiodesis group, the mean LLD before epiphysiodesis was 2.7 cm (95% CI 1.3 to 3.4) and 1.3 cm (95% CI -0.5 to 3.8) at skeletal maturity. In the nonepiphysiodesis group the mean LLD was 2.0 cm (95% CI 0.5 to 5.1; p = 0.016). The subtrochanteric region on the PD side was significantly longer at skeletal maturity in the epiphysiodesis group compared to the nonepiphysiodesis group (-1.0 cm (95% CI -2.4 to 0.6) vs 0.1 cm (95% CI -1.0 to 2.1); p < 0.001). Conclusion: This study demonstrates that LLD after PD originates from the proximal segment only. In patients who had contralateral epiphysiodesis to balance leg length, this is achieved by creating a difference in subtrochanteric length. Arthroplasty surgeons need to be aware that shortening of the proximal femur segment in PD patients may be misleading, as the ipsilateral subtrochanteric length in these patients can be longer. Therefore, we strongly advise long-leg standing films for THA planning in PD patients in order to avoid inadvertently lengthening the limb. Cite this article: Bone Joint J  2021;103-B(11):1736–1741.